Relevansi Penunjukkan BUMN Selaku Pemungut PPN (WAPU) di Era e-faktur - Daris, Fiki Taufik; Ependi, Acun; Setyawati, Dinie; Marcelina, Meta (JPAK : Jurnal Pendidikan Akuntansi dan Keuangan, 2020)
In order to improve compliance and secure tax revenue, the Directorate General of Taxes appoints State-Owned Enterprises (SOEs) and several subsidiary entities as VAT Collectors, so that the collection and deposit obligations shift to VAT Collectors along with the consequences of sanctions. However, based on The Audit Board of Indonesia's audit report, it is known that there are VATs that have not yet been deposited and there are delays in depositing VAT which can result in potential tax fines. In 2016 DGT launched e-tax invoice application that aims to improve services and facilitate supervision of taxable entrepeneur. This paper was made using a literature review research method that examines theory, regulation, and implementation that is associated with the development of taxation applications, namely e-tax invoice. The results of the study showed that there were recommendations for considerations in evaluating the changes in regulations or evaluating the appointment of certain SOEs and Agencies as VAT collectors.